Assessment of Skater`s Movements Technique outside the Ice Surface Based on Foot Interaction with the Support - Bykov, D. (Sporto Mokslas-Sport Science, 2017)
Technical training of skaters is a quite specific process due to the peculiarities of training both in the ice surface and outside it. One of the main means for improvement of technical readiness of skaters outside the ice surface is a special imitation exercises.